Ethylene enhances transcriptions of asparagine biosynthetic genes in soybean (Glycine max L. Merr) leaves - Gyeongik Ahn; Yeong Jun Ban; Gyeong-Im Shin; Song Yi Jeong; Ki Hun Park; Woe-Yeon Kim; Joon-Yung Cha (Plant Signaling & Behavior, 2023)
Soybean, a vital protein-rich crop, offers bioactivity that can mitigate various chronic human diseases. Nonetheless, soybean breeding poses a challenge due to the negative correlation between enhanced protein levels and overall productivity. Our previous studies demonstrated that applying gaseous phytohormone, ethylene, to soybean leaves significantly boosts the accumulation of free amino acids, particularly asparagine (Asn). Current studies also revealed that ethylene application to soybeans significantly enhanced both essential and non-essential amino acid contents in leaves and stems. Asn plays a crucial role in ammonia detoxification and reducing fatigue. However, the molecular evidence supporting this phenomenon remains elusive. This study explores the molecular mechanisms behind enhanced Asn accumulation in ethylene-treated soybean leaves. Transcriptional analysis revealed that ethylene treatments to soybean leaves enhance the transcriptional levels of key genes involved in Asn biosynthesis, such as aspartate aminotransferase (AspAT) and Asn synthetase (ASN), which aligns with our previous observations of elevated Asn levels. These findings shed light on the role of ethylene in upregulating Asn biosynthetic genes, subsequently enhancing Asn concentrations. This molecular insight into amino acid metabolism regulation provides valuable knowledge for the metabolic farming of crops, especially in elevating nutraceutical ingredients with non-genetic modification (GM) approach for improved protein content.